Gambaran Klinis dan Histopatologis Limfoma Non Hodgkin Sistem Pencernaan di RSUP Dr. Hasan Sadikin Bandung Tahun 2018-2020 - Maharani Tasyandita, Raina; Suryawathy Hernowo, Bethy; Yulianti, Herry (Majalah Patologi Indonesia, 2023)
BackgroundNon-Hodgkin's lymphoma (NHL) is an abnormal growth of lymphocytes that manifests as tumor or enlargement of lymph nodes (lymphadenopathy). New NHL cases in Indonesia in 2020 reached 16.125 cases (4.1%) with 9.024 deaths (3.6%). The WHO classification categorizes NHL into two, B cells and T/NK cells.2 NHL is also divided into low-grade and high-grade based on its progression. The gastrointestinal tract is the most frequently involved extranodal site in NHL. The clinical manifestations of NHL can be non-specific and vary depending on anatomic location. This study aims to determine the clinical and histopathological features in patients with gastrointestinal NHL.MethodsThis research is a descriptive study using medical record data of inpatients at RSUP Dr. Hasan Sadikin Bandung period 2018-2020 diagnosed with gastrointestinal NHL.ResultsPatient characteristics were dominated by patients aged 40 years and male (65.2%), with the most clinical manifestations being enlarged lymph nodes. NHL most often attacks the liver (26.1%) and most patients present at stage IV (34.8%). The most histopathological features were B cells (52.5%) and high-grade (43.5%).ConclusionThe risk of gastrointestinal LNH increases with age and the majority is in men. Clinical manifestations vary and can show local or constitutional symptoms. Most patients are found to be in the late stages and among all gastrointestinal system, most NHL attacks the liver. Many patients were not subjected to further immunohistochemical examination, but the most common histopathological features were B cells and high grade NHL.